Założenia reformy gospodarczej - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1982)
The article discusses the foundations of the economic reform in Poland. It presents interrelations existing among political, economic and social factors in defining these foundations. The economic reform requires a new definition of relations among the Party, trade unions, the administrative board and various social groups. Particularly important is to guarantee a real part in governing to the people. In the domain of economic relations, it is necessary both to restore the active role in forming of the economic activity to the money and to secure the independence of enterprises. Market should constitute the crucial facta in shaping of the economic activity. Production land services should comply, with the demand of the market. This, "however, requires the elimination of centrally established limitations. The need of price reform being a fragment of the whole economic reform, has also been underlined in the article. The author strongly declares for making the most of human interest and motivation in the improvement of the economic situation.
The Foundations of the Economy Reform